Antese de flores-de-pólen em dependência de chuva ou seca no semi-árido - Sousa, Juliana Rodrigues de (2010)
The majority of flowers evolved a dependence of bees as pollinators. While on one side the bees need pollen as brood food, species with flowers pollinated by bees show mechanisms to safeguard at least part of their pollen for pollination. Pollen-only flowers possess just pollen to attract pollinators. It is generally contained in poricidal anthers from where it can be removed exclusively by certain bees able to sonicate the flower. For this mechanism to function pollen has to be dry. To flower, however, the plants need water. To understand the relation between precipitation and blooming of pollen-only flowers, we observed the flowering phenology of six caatinga species in the Cariri, southern Ceará. As presupposed, flower production occurred during the dry season in the majority of the observed species. Senna acuruensis, Cochlospermum vitifolium and Chamaecrista curvifolia had their peaks in the dry season, while Senna spectabilis flowered exclusively in the rainy part of the year. Solanum paniculatum had its main peak in the dry season but produced a minor one also in the wet season. The exotic Senna siamea showed blooms year-round. All species demonstrated an elevated (>60%) percentage of flowering synchrony. As the antheses for many months did not fit the patterns described by Gentry (1974) for nectar flowers, we coined the term “macropedosy” (from greek μακρός = of long duration and παιδοῦς = with abundant children; responsible for much offspring during long time) for this behaviour. Only in S. spectabilis and S. siamea, flowering was positively related to precipitation. In the other species, it was negatively related, except S. acuruensis, that demonstrated no correlation at all. Visits of vibrating bees occurred during dry spells. We thus conclude that the dry conditions necessary for buzzing in pollen-only flowers are met with independently of dry or wet season.